OP61 Perceived maternal stress and emotional wellbeing as risk factors for miscarriage. (2nd September 2014) - Meaney, S; Corcoran, P; Lutomski, JE; Gallagher, S; Spillane, N; O'Donoghue, K
Abstract : Background: Miscarriage is the most common adverse outcome in pregnancy. Investigations suggest numerous risk factors however the cause remains poorly understood. The study aimed to examine the contribution of an array of psychological factors to risk of miscarriage. Methods: A cohort study was conducted in a large, tertiary hospital (8500 deliveries per annum) in the Republic of Ireland in 2012. Women randomly selected at their first booking visit (10–14 weeks) were asked to complete a detailed lifestyle questionnaire, which included common risk factors for miscarriage. Emotional wellbeing, social support, life orientation and perceived stress were assessed using the following validated psychometric tests; the RAND 36-Item Health Survey, the Maternity Social Support Scale, the Revised Life Orientation Test and the Perceived Stress Scale. All participants were followed up at 20 weeks gestation to determine pregnancy outcome. Logistic regression was conducted to assess associations with risk of miscarriage. Results: Of the 417 participants, 32.1% (n = 134) had a confirmed miscarriage at follow-up. After adjustment, women with high levels of perceived stress had increased odds of miscarriage (OR 1.97, 95% CI 1.14–3.44) relative to women with low perceived stress (44.1% vs. 26.0%). While high emotional wellbeing was somewhat protective (OR 0.68, 95% CI 0.38–1.11) relative to women with low emotional wellbeing (26.8% vs. 35.9%). Maternal social support and life orientation were not associated with miscarriage. Conclusion: Perceived stress and low emotional wellbeing may increase risk of miscarriage. Early assessment and greater support to vulnerable women may be important and warrants further investigation.